A short stereoselective synthesis of (+)-(6R,2′S)-cryptocaryalactone via ring-closing metathesis - Radha Krishna, Palakodety; Lopinti, Krishnarao; Reddy, K. L. N. (Beilstein Journal of Organic Chemistry, 2009)
A short stereoselective synthesis of (+)-(6R,2′S)-cryptocaryalactone was successfully completed. Key steps included the application of Carreira’s asymmetric alkynylation reaction to form a propargylic alcohol and subsequently lactone formation using the powerful ring-closing metathesis reaction.
Keywords: Carreira asymmetric alkynylation; Cryptocarya bourdilloni GAMB (Lauraceae); ring-closing metathesis; Sharpless asymmetric epoxidation